Comparative transcriptome analysis of long non coding RNA (lncRNA) in RTG-2 cells infected by infectious hematopoietic necrosis virus. Issue 120 (January 2022) - Ren, Guangming; Xu, Liming; Zhao, Jingzhuang; Shao, Yizhi; Lu, Tongyan; Zhang, Qiya
Abstract: Infectious hematopoietic necrosis virus (IHNV) is the vital pathogen that has caused the great economic loss in salmonid fisheries. To date, there is limited information concerning the changes of lncRNAs in RTG-2 cells infected by IHNV. In this study, a comparative transcriptome analysis of lncRNAs was performed in RTG-2 cells with and without IHNV infection to determine their changes and the effects on IHNV infection. The results showed that IHNV infection significantly changed the expression levels of lncRNAs and mRNAs, including 3693 differentially expressed lncRNAs (DE-lncRNAs) and 3503 differentially expressed mRNAs (DE-mRNAs) respectively. These DE-lncRNAs and DE-mRNAs induced by IHNV were mostly associated with immune response, RNA processing, and viral diseases related pathways. Further analysis found that some DE-lncRNAs might participate in the regulation of extracellular matrix metabolism, apoptosis, lipid synthesis, autophagy, and immune responses referring to the functions of their target genes. Afterwards, 349 co-expression relationships were constructed by 223 DE-lncRNAs and 271 DE-mRNAs, of which LTCONS_00146935 was the pivotal node in the interaction networks, and was together with its target genes modulated the immune responses under the IHNV infection. RT-qPCR results showed that the changes of the selected immune-related DEGs were in consistent with the RNA-seq data, suggesting that the sequencing data was relatively reliable. In summary, this is the first study to determine the changes and interactions of lncRNA-mRNA in RTG-2 cells under the IHNV infection. The results provided the valuable information concerning the lncRNAs in salmonid fish, which will benefit for future study on uncovering the roles of lncRNAs-mRNAs during the viral infection. Highlights: Comparative transcriptome analysis of lncRNAs was performed in RTG-2 cells with and without IHNV infection. IHNV infection significantly changed the expression levels of lncRNAs and mRNAs. DE-lncRNAs might participate in regulating many immune processes referring to the functions of their target genes.